Associations of Sleep Insufficiency and Chronotype with Inflammatory Cytokines in College Students - Zhai S (Dove Medical Press, 2021)
Shuang Zhai,1 Shuman Tao,2,3 Xiaoyan Wu,1,3 Liwei Zou,1 Yajuan Yang,4 Yang Xie,1 Tingting Li,1 Dan Zhang,1 Yang Qu,1 Fangbiao Tao1,3 1Department of Maternal, Child & Adolescent Health, School of Public Health, Anhui Medical University, Hefei, People’s Republic of China; 2Department of Nephrology, The Second Hospital of Anhui Medical University, Hefei, People’s Republic of China; 3MOE Key Laboratory of Population Health Across Life Cycle/NHC Key Laboratory of Study on Abnormal Gametes and Reproductive Tract, Hefei, People’s Republic of China; 4School of Nursing, Anhui Medical University, Hefei, People’s Republic of ChinaCorrespondence: Shuman TaoDepartment of Nephrology, The Second Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of ChinaTel +86 15077927106Email shumantao@126.comPurpose: Sleep insufficiency and circadian rhythm disturbances in college students have become prominent. Current findings show that sleep insufficiency is closely related to inflammation. Studies on the correlation between chronotype and inflammatory factors are still lacking. Therefore, this research intended to examine the relationships between sleep duration, chronotype and inflammatory cytokines in young adults, and to estimate the correlation between chronotype and inflammatory cytokines stratified by sleep duration.Patients and Methods: We conducted a cross-sectional study in April and May 2019. Participants were recruited from two colleges located in central China. The Pittsburgh Sleep Quality Index (PSQI) and the Morning and Evening Questionnaire-5 (MEQ-5) were administered to assess sleep duration and chronotype. Sleep duration less than 7 hours was defined as insufficient sleep. Fasting venous blood was collected to measure plasma levels of inflammatory markers including IL-1β, IL-6, TNF-α and IL-10.Results: A total of 723 participants were included in this study, with a mean age of 18.68 years (standard deviation=0.99). After adjusting for confounding factors, the results of generalized linear model showed that sleep insufficiency was positively correlated with IL-1β, TNF-α and IL-10; and evening-types (E-types) were positively associated with the levels of IL-1β and IL-6 (p< 0.05). Compared to the control group (sleep sufficiency and M-types), there were positive interaction effects of sleep insufficiency and neutral-types (N-types) on the levels of IL-1β, IL-6, TNF-α and IL-10 (p< 0.05). The hierarchical regression model showed that N-types and E-types were positively correlated to the levels of IL-1β, IL-6, TNF-α and IL-10 among college students with sleep insufficiency (p< 0.05).Conclusion: The levels of inflammatory markers were higher among college students with sleep insufficiency and E-types. N-types and E-types were positively correlated with IL-1β, IL-6, TNF-α and IL-10 among college students with sleep insufficiency.Keywords: sleep duration, circadian rhythm, chronic inflammation, young adults